1989
DOI: 10.1002/aja.1001860406
|View full text |Cite
|
Sign up to set email alerts
|

Covalent affinity labeling, radioautography, and immunocytochemistry localize the glucocorticoid receptor in rat testicular leydig cells

Abstract: The presence and distribution of glucocorticoid receptors in the rat testis were examined by using 2 approaches: in vivo quantitative radioautography and immunocytochemistry. Radioautographic localization was made possible through the availability of a glucocorticoid receptor affinity label, dexamethasone 21-mesylate, which binds covalently to the glucocorticoid receptor, thereby preventing dissociation of the steroid-receptor complex. Adrenalectomized adult rats were injected with a tritiated (3H) form of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
31
0

Year Published

1991
1991
2008
2008

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(40 citation statements)
references
References 35 publications
5
31
0
Order By: Relevance
“…Sertoli cells, which produce IL-1 constitutively, do not appear to produce IL-1 , but rat and human Leydig cells express IL-1 in response to inflammatory stimulation in vitro (Lin et al 1993, Cudicini et al 1997, Jonsson et al 1999. It is possible that, even though the Leydig cells possess glucocorticoid receptors ( Stalker et al 1989), the production of IL-1 by these cells may not be responsive to glucocorticoid control due to differences in the regulatory regions of the IL-1 gene, for example. Alternatively, the different effects of DEX on IL-1 mRNA in the testis and liver might be explained by differential access of DEX to the two organs.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Sertoli cells, which produce IL-1 constitutively, do not appear to produce IL-1 , but rat and human Leydig cells express IL-1 in response to inflammatory stimulation in vitro (Lin et al 1993, Cudicini et al 1997, Jonsson et al 1999. It is possible that, even though the Leydig cells possess glucocorticoid receptors ( Stalker et al 1989), the production of IL-1 by these cells may not be responsive to glucocorticoid control due to differences in the regulatory regions of the IL-1 gene, for example. Alternatively, the different effects of DEX on IL-1 mRNA in the testis and liver might be explained by differential access of DEX to the two organs.…”
Section: Discussionmentioning
confidence: 98%
“…Glucocorticoids exert a negative feedback effect on the inflammatory response by reducing the production, secretion and actions of the principal inflammatory mediators, such as IL-1 , and are widely used clinically as anti-inflammatory agents (Kapcala et al 1995). However, glucocorticoids also inhibit testicular steroidogenesis by actions at the hypothalamus and pituitary (Bambino & Hsueh 1981), and by direct inhibition of P450scc, 3 -hydroxysteroid dehydrogenase and P450c17 levels (Sapolsky 1985, Hales & Payne 1989, Monder et al 1994, Gao et al 1996, acting through specific receptors on the Leydig cells (Stalker et al 1989). Glucocorticoid levels are elevated for 4-6 h following LPS treatment in humans and experimental animals (Wolff 1973, Stenzel-Poore et al 1993.…”
Section: Introductionmentioning
confidence: 99%
“…Apparently, the classic GRs are involved in these glucocorticoid actions. Leydig cells express classic GRs [19][20][21]. The Leydig cell responds to glucocorticoids.…”
Section: Stress and Leydig Cell Functionmentioning
confidence: 99%
“…Leydig cells express the Gc receptor (GR,NR3C1) and are the main targets of Gc action in the testis (Evain et al 1976, Stalker et al 1989, Schwarzenbach et al 2003. Although the molecular mechanisms by which Gc decrease steroidogenesis have not been entirely defined, numerous studies have shown that Gc can inhibit expression of enzymes involved in testosterone biosynthesis such as Star, Cyp11a1, Cyp17a1, Hsd3b and Hsd17b3 (Hales & Payne 1989, Payne & Sha 1991, Wang et al 2000, Huang & Shirley 2001, Schwarzenbach et al 2003, Badrinarayanan et al 2006, Fon & Li 2007.…”
Section: Introductionmentioning
confidence: 99%